Application Of Mechanical Dryer For Strenghtning Of Production Capability Of "Potato Crackers" Industry To Fulfill Market Demand - Wignyanto Wignyanto (Journal of Innovation and Applied Technology, 2015)
ABSTRACTThe purpose of this activity is the application of dryer machine in potato crackers industry to strengthen production capabilities and fulfillment of market demand. There were several activities that had done,  beginning: 1) survey to “Dua Merpati” SMEs in Batu regency and do primary evaluation, 2) design  and create dryer machine 3) training 4) implementation of machine in SMEs, and 5) last evaluation and mentoring. The results showed that the application of dryer machine rack type can increase production capabilities and maintain continuity of production during the wet season, so as to meet the demand. Dryer machine that has implemented the specification: The dimensions of the drying chamber 3 x 3 meters with 126 trays, trays dimensions 30 x 70 cm, dryer capacity is 1000 kg of wet crackers/process. Performance of the dryer is to achieve a moisture content of 9 % takes 3 hours. This saves time by 50 %, where before with sun drying takes at least 6 hours. It means that the application of dryer machine in SMEs “Dua Merpati”  can improve the performance of it’s production system, product quality, efficiency, productivity and keep the production continuity.Keywords : potato cracker, dryer machine